Sodium and potassium excretion and its association with cardiovascular disorders in Mexican adults - Campos Nonato, Ismael; Mendoza, Kenny; Vargas Meza, Jorge; Flores Aldana, Mario; Barquera, Simón (Frontiers in Nutrition, 2024)
Worldwide, as well as in Mexico, the leading cause of death is cardiovascular disease (CVD). Hypertension is the main risk factor for CVD; about 50% of the adult population suffers from this condition. High sodium (Na) intake combined with low potassium (K) intake can trigger cardiovascular disorders such as high blood pressure (BP). The aim of this study was to estimate the mean excretion of Na and K in Mexican adults using a spot urine sample, and its association with cardiovascular disorders. Information on 2778 adults, 20-59 years of age, who participated in ENSANUT-2016 was analyzed. Na and K were estimated using Tanaka formulae. Biomarkers such as glucose, total cholesterol, triglycerides, HDL cholesterol and LDL cholesterol, and anthropometry were measured. Mean Na was 3354 mg/day (95%CI: 3278, 3429), 1440 mg/day of K (95%CI: 1412, 1469), and the Na-K ratio was 2.4. The excretion of Na was greater in adults with high BP (3542 mg/day) compared to those with normal BP (3296 mg/day). In adults with hypertension, excretion of K was 10% greater (1534 mg/ day) than in adults with normal BP (1357 mg/day). In adults with moderate reduction of renal function, Na excretion was 22% less (2772 mg/day) than in adults with normal kidney function (3382 mg/day). The results of this study show that the cardiovascular health of Mexican adults is at risk, as they showed high Na excretion and low K excretion.